DEVELOPMENT OF RW CHAIRMAN SELECTION APPLICATION WEB USING CODEIGNITER, PHP AND MYSQL FRAMEWORK - Adam Huda Nugraha (Lembaga Pengembangan Kinerja Dosen, 2021)
E-Voting is the use of computer technology for the implementation of voting. One choice of computer technology used for the implementation of e-voting is to use a client-server architecture. So the use of an all-computer-based-system is expected to replace the manual voting process. The goal to be achieved from making this e-voting application is to be able to assist committee officers in calculating the number of voters and calculating election results quickly and accurately. This application is made using the PHP programming language which is expected to overcome problems related to selection. In making this website, the stages carried out are, preparing the required data, designing the website, designing input and output, followed by the implementation stage of making program coding, the last stage is the trial stage on localhost. Planned trials that set up the application to run properly.